ANALISIS BIBLIOMETRIK PENELITIAN PARIWISATA SYARIAH HALAL DI INDONESIA MELALUI DATABASE SCOPUS - Irfan Harmoko (Reinforce: Journal of Sharia Management, 2023)
The purpose of this research is to analyze the bibliometric characteristics and trends in scholarly publications on halal tourism in Indonesia based on the Scopus database. Data collection was conducted in March 2023, using the search keyword "halal tourism in Indonesia." The data was retrieved from the Scopus database from 2016 to the first quarter of 2023. The data was processed using the Vos Viewer application. The study results indicate that the number of scholarly publications in the Scopus database related to halal tourism in Indonesia has increased. The most popular journal in this field is the Journal of Islamic Marketing. The dominant document type is articles. The most influential authors are Wardi Y., Abror A., and Trinanda O., affiliated with Universitas Negeri Padang, with seventy-four citations. There are six research clusters based on keyword searches. The keywords "economic growth" and "perceived value" emerged as significant in the latest research in 2022. These keywords are strongly related to halal tourism, indicating that future research opportunities using these keywords have a high level of novelty. Additionally, this research also provides nine recommendations for future studies on the theme of halal tourism in Indonesia.